The Analysis of Grade VIII Spatial Visual Abilities at SMP Negeri 3 Ampibabo in Understanding the Concept of a Quartend Based on Van Hiele’s Geometry Thinking Levels - Janah, Nur; Sukayasa, Sukayasa; Ismaimuza, Dasa; Meinarni, Welli (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
This research aims to describe students' visual spatial abilities in understanding the concept of quadrilaterals in terms of the Van Hiele level of geometric thinking. The subjects in this research were 3 students who met each level of Van Hiele geometric thinking starting from level 0, level 1, and level 2 in class VIII students at SMP Negeri 3 Ampibabo. Data collection methods in this research are tests, including the Van Hiele test as well as visual spatial ability task sheets and interviews conducted by researchers with subjects which are based on data analysis carried out by researchers. The results of the research show that students who are at the Van Hiele level of geometric thinking, where students who are at level 0, do not all meet the indicators of visual spatial ability in imagination which is the most dominant indicator, but there are still errors in thisdepicting a quadrilateral, while students who are at level 1-2 fulfill the visual-spatial ability indicators of imagining, conceptualizing, problem solving, and pattern searching.